Implementasi Pendidikan Berbasis Budaya pada Pembelajaran Bahasa Inggris di SDN Salembaran 3 Tangerang - Sintawati, Fairus (JEDLISH : Journal Of Education and English Language Teaching, 2021)
This study aims to describe the planning, implementation, assessment, and barriers to culture-based elementary English learning at SDN Salembaran 3. This study uses a qualitative method with the type of case study. The subjects of this study were English teachers, school principals, and students at SDN Salembaran 3. Data collection techniques in this study used three types, namely: observation, interviews and documentation. Data were analyzed and described and tested for validity through triangulation of methods and sources. The results of the study concluded that in planning for culture-based education in learning English the teacher had incorporated cultural elements into the lesson plan (RPP) and the syllabus was developed according to the context and potential of each school. At the implementation stage, there are teachers who have used texts and videos that contain cultural elements to introduce culture and art to students, such as Lenggang Cisadane Dance, Gambang Kromong Art, Lenong Art, and Lion Dance and introduce them to students in three languages, namely English, Bahasa Indonesia Indonesian, and Sundanese. Students are also stimulated for responses in English. Finally, at the evaluation stage, an assessment format is used in accordance with the guidebook for implementing culture-based education which measures students' ability to use English appropriately according to basic competencies and learning indicators.